2020
DOI: 10.1007/s12253-020-00835-x
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Aortic Aneurysm and Dissection Related Death: an Autopsy Database Analysis

Abstract: Acute aortic catastrophes (AAC), mainly ruptured aneurysms and dissections, lead all other vascular conditions in morbidity and mortality, even if intervention occurs. The aim of our study was to give a descriptive overview of the demographic and pathological characteristics of AAC. Between 1994 and 2013, 80,469 autopsies were performed at Semmelweis University hospitals in Budapest. After collecting the autopsy reports we were able to create the AAC database upon which we conducted our analysis. We found 567 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
3
1
1
Order By: Relevance
“…A previous study had reported that among patients with ruptured TAA, prehospital death was highest for TAA-asc. 10 We could not find any significant differences in patient characteristic between the 5 groups of aortic aneurysms, and between the broadly defined TAA group (TAA and TAAA) and AAA group. A recent study reported that AAA was more strongly associated with atherosclerosis than TAA.…”
Section: Discussioncontrasting
confidence: 53%
“…A previous study had reported that among patients with ruptured TAA, prehospital death was highest for TAA-asc. 10 We could not find any significant differences in patient characteristic between the 5 groups of aortic aneurysms, and between the broadly defined TAA group (TAA and TAAA) and AAA group. A recent study reported that AAA was more strongly associated with atherosclerosis than TAA.…”
Section: Discussioncontrasting
confidence: 53%
“…Autopsy studies have revealed that the most common cause of death due to AA is rupture [6]. This highlights the critical need for developing a standardized screening technique for early diagnosis to mitigate life-threatening complications.…”
Section: Significancementioning
confidence: 99%
“…An autopsy study revealed that 50% of type A dissections in emergency departments remain undetected [ 19 ]. In another autopsy study, which was carried out in Hungary where all sudden deaths undergo an autopsy, it was shown that only 6% of the patients with ruptured aortic dissection reached hospital [ 20 ].…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%